Occupational stress and job satisfaction of healthcare staff in rehabilitation units / Stress e soddisfazione lavorativa degli operatori sanitari nei reparti di riabilitazione - Fiabane, Elena; Giorgi, Ines; Musian, Daniele; Sguazzin, Cinzia; Argentero, Piergiorgio (La Medicina del Lavoro, 2012)
SummaryBackground: Occupational stress and job dissatisfaction are recognized risk factors for healthcare professionals and can lead to a decrease in work performance and in the quality of care offered, and to poorer health of workers. Research in the rehabilitation care setting is very limited and needs to be explored. Objectives: To investigate occupational stress, job satisfaction and their relationships with organizational factors among healthcare staff in rehabilitation units. Methods: A cross-sectional study of healthcare staff working in two rehabilitation units was conducted. They were sent two self-administered questionnaires, the Occupational Stress Indicator (OSI) and the Areas of Work life Scale (AWS), in order to assess occupational stress and job satisfaction. One-way ANOVA was used to explore work stress among two groups of workers, characterized by high and low job satisfaction levels. Stepwise multiple linear regression analysis was conducted to assess the association between job satisfaction and organizational risk factors. Results: A total of 90 questionnaires were returned (response rate 53%). The main sources of stress were unfairness, conflict between personal and organizational values, lack of reward and workload. Workers with low job satisfaction significantly scored higher in work-related stress in regard to various aspects of work, and in lower job control. Regression analysis showed that the most important predictors of job satisfaction were fairness and workload. Conclusions: The results of this study showed that job dissatisfaction is strongly associated with work stress and certain organizational risk factors. This study suggests the importance of focusing on the psychosocial factors in the work environment and job satisfaction in order to improve the well-being of rehabilitation healthcare staff.Riassunto«Stress e soddisfazione lavorativa degli operatori sanitari nei reparti di riabilitazione». Introduzione: Lo stress e l’insoddisfazione lavorativa rappresentano importanti fattori di rischio per le professioni sanitarie; negli ultimi anni la richiesta di servizi di riabilitazione è in costante aumento, ma solo pochi studi hanno investigato la salute occupazionale in questo specifico settore della medicina. Obiettivi: La ricerca ha l’obiettivo di identificare le principali cause di insoddisfazione e stress lavorativo nei reparti di riabilitazione. Metodi: Il personale sanitario di due reparti di riabilitazione è stato invitato a compilare i questionari Occupational Stress Indicator (OSI) e Areas of Work life Scale (AWS) per la valutazione della percezione di stress e della soddisfazione lavorativa. I dati raccolti sono stati elaborati attraverso analisi descrittive, della varianza e modelli di regressione multipla. Risultati: Il campione totale è costituito da 90 operatori sanitari (pari al 53% dei questionari consegnati). Le principali fonti di stress lavorativo riguardano la percezione di scarsa equità, l’incongruenza tra i valori personali e dell’organizzazione, la mancanza di riconoscimento e il carico di lavoro. Gli operatori meno soddisfatti mostrano valori significativamente maggiori di stress lavorativo e una percezione di minore controllo sul proprio lavoro. I più importanti predittori della soddisfazione lavorativa sono risultati essere la percezione di equità e il carico di lavoro. Conclusioni: L’insoddisfazione lavorativa è fortemente associata alla percezione di stress e a specifici fattori di rischio organizzativo. Il presente studio evidenzia l’importanza di valutare i fattori lavorativi di tipo psicosociale, e in particolare la soddisfazione professionale, al fine di promuovere il benessere degli operatori e migliorare l’attività lavorativa nei reparti di riabilitazione.